Sef1-Regulated Iron Regulon Responds to Mitochondria-Dependent Iron–Sulfur Cluster Biosynthesis in Candida albicans - Ror, Shivani; Panwar, Sneh Lata (Frontiers in Microbiology, 2019)
Iron homeostasis mechanisms allow the prime commensal-pathogen Candida albicans to cope with the profound shift in iron levels in the mammalian host. The regulators, Sef1 and Sfu1 influence activation and repression of genes required for iron uptake and acquisition by inducing the expression of iron regulon genes in iron-deplete conditions and inactivating them in iron-replete condition. Our study for the first time shows that C. albicans coordinates the activation of the iron regulon with the mitochondrial use of iron for Fe-S cluster biosynthesis, a cellular process that is connected to cellular iron metabolism. We took advantage of a mutant defective in mitochondrial biogenesis (fzo1∆/∆) to assess the aforesaid link as this mutant exhibited sustained expression of the Sef1 iron regulon, signifying an iron-starved state in the mutant. Our analysis demonstrates that mitochondrion is pivotal for regulation of Fe-S cluster synthesis such that the disruption of this cellular process in fzo1∆/∆ cells lead to excessive mitochondrial iron accumulation and reduced activity of the Fe-S cluster-containing enzyme aconitase. Sef1 responds to defective Fe-S cluster synthesis by regulated changes in its subcellular localization; it was retained in the nucleus resulting in the induced expression of the iron regulon. We predict that the mitochondrial Fe-S assembly generates a molecule that is critical for ensuring iron-responsive transcriptional activation of the Sef1 regulon. All told, our data marks Fe-S biogenesis as a mechanism that meshes cellular iron procurement with mitochondrial iron metabolism resulting in regulating the Sef1 regulon in C. albicans.